TINJAUAN YURIDIS TERHADAP UPAYA HUKUM YANG DILAKUKAN OLEH ANGGOTA DEWAN PERWAKILAN DAERAH AKIBAT DIBERHENTIKAN OLEH BADAN KEHORMATAN DPD RI - Agustinus Hitri Liberty D. Kalumbang,; Erikson Sihotang,; I Nyoman Suandika, (Nusantara Hasana Journal, 2024)
The implementation of a bicameral system in the state order of the Unitary State of the Republic of Indonesia raises questions about the role and authority of the DPD RI fittings, namely the Honorary Body, the validity of a decision in the appointment and dismissal of the chairman of the DPD RI who is affected by a corruption case. The authority of the Honorary Body of DPD RI is authorized to conduct internal supervision of DPD RI through investigation and verification of a complaint and determine a decision in the decision-making deliberation, must be based on applicable rules and appropriate systems. The purpose of this study is to explain and describe the role of the DPD Honorary Board in the dismissal of DPD RI members, as well as to find out the validity of the dismissal of DPD RI members carried out by the DPD RI Honorary Body. The method used in the preparation of this study is normative research. Normative legal research includes, research on legal principles, research on legal systematics, research on the level of legal synchronization, research on legal history, and legal comparison. The result of this study is the first that the authority of the Honorary Board of DPD RI in supervising violations of the DPD RI code of ethics is so significant because its duties and authorities are to investigate and verify complaints, determine decisions, submit results, internal supervision, evaluation and improvement of discipline. Second, that the Validity of the Dismissal of DPD RI Members by the Honorary Board of DPD RI has been written in the Regulation of the Regional Representative Council of the Republic of Indonesia no. 1 of 2022 concerning rules of conduct. Interim Stops; Article 25 (2), Procedures for Interim Dismissal of DPD RI Members are contained in; Article 26; Article 27; Article 28, Temporary Suspension; Article 31, Procedures for Temporary Dismissal; Article 32. Legal remedies carried out by DPD Members who were dismissed by the Honorary Board of DPD RI, are based on Law No. 17 of 2014 concerning the Right to Self-Defense article 289 and concerning the Right to Immunity article 290, as well as Regulation of the Regional Representative Council of the Republic of Indonesia no. 1 of 2022; About the Right to Self-Defense Article 20; and About the Right to Immunity article 21.